Turner disease: a contemporary clinical approach - Tančić Gajić, Milina; Tesla, Bojana; Miletic, Marija; Stojanovic, Milos; Vujovic, Svetlana (Medical Research, 2025)
Turner syndrome (TS) is a rare genetic disorder in females caused by partial or complete loss of one X chromosome. It presents with multisystem clinical manifestations that require lifelong multidisciplinary care and monitoring. Phenotypically, TS is characterized by short stature, short neck with lateral skin folds (pterygium colli), low-set ears, and a low posterior hairline. Clinically, it is associated with cardiovascular diseases (CVD) and primary hypogonadism. The diagnosis of TS is based on clinical presentation and genetic analysis, with early prenatal detection possible. In newborns, TS should be suspected in the presence of oedema of the hands and feet. Short stature becomes evident in early childhood, while delayed puberty and primary amenorrhea are common later findings. CVDs may be congenital or acquired; coarctation of the aorta is a key diagnostic sign, whereas aortic dissection and rupture of an aortic aneurysm are life-threatening complications. Most women with TS have primary hypogonadism and high infertility rates. Spontaneous pregnancies are rare, and fertility preservation options, such as oocyte or embryo cryopreservation, should be considered early. Associated autoimmune diseases, kidney anomalies, liver disorders, and hearing loss are also common. Hormone replacement therapy is essential for pubertal induction, maintenance of general health, and prevention of long-term complications of untreated hypogonadism. Due to numerous comorbidities and variable phenotypes, an individualized multidisciplinary approach is required. With early diagnosis, appropriate management, and psychosocial support, individuals with TS can lead a good quality of life despite ongoing health risks.
Keywords: Turner syndrome, Turner syndrome genetics, premature ovarian insufficiency, hormone replacement treatment